2020
DOI: 10.3390/ma13051083
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Alveolar Ridge Dimensions Utilizing an Extracted Tooth Dentin Particulate Autograft and Platelet-Rich fibrin: A Retrospective Radiographic Cone-Beam Computed Tomography Study

Abstract: This study utilized radiographic comparative analysis in order to evaluate dimensional ridge changes four months after tooth extraction and immediate grafting with mineralized dentin particulate autograft and chopped platelet-rich fibrin. Fifty-eight extraction sockets with up to 2 mm of missing buccal bone in the coronal aspect compared to the lingual bone were included. Graft material was covered with either a platelet-rich fibrin membrane or collagen sponge with no effort to achieve primary closure. The dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Regarding the preparation of autogenous dentin for grafting, the present trial used the LTM without removing the enamel, following other authors such as Kabir et al [20] or Minetti et al [33] who conducted a clinical trial of alveolar preservation using dentin and enamel. Others such as Valdec et al [17] removed the enamel, pulp and cementum, while Pohl et al [34] removed the enamel from the crown and Del Canto et al [18] and Schwarz et al [35] used only the roots, having removed the radicular cementum.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the preparation of autogenous dentin for grafting, the present trial used the LTM without removing the enamel, following other authors such as Kabir et al [20] or Minetti et al [33] who conducted a clinical trial of alveolar preservation using dentin and enamel. Others such as Valdec et al [17] removed the enamel, pulp and cementum, while Pohl et al [34] removed the enamel from the crown and Del Canto et al [18] and Schwarz et al [35] used only the roots, having removed the radicular cementum.…”
Section: Discussionmentioning
confidence: 99%
“…While some investigators have reported success when using DDM (or PDDM) [17,37,39,40,44,[48][49][50] others prefer using in its undemineralized form [38,[51][52][53][54][55][56][57].…”
Section: Dentin Processingmentioning
confidence: 99%
“…In terms of UDD, a solid number of preclinical and clinical studies have been performed evaluating its efficacy [38,[51][52][53][54][55][56][57]68].…”
Section: Undemineralized Dentin Matrix (Udd)mentioning
confidence: 99%
See 2 more Smart Citations